NGF (−198C > T, Ala35Val) and p75 NTR (Ser205Leu) gene mutations are associated with liver function in different histopathological profiles of the patients with chronic viral hepatitis in the Brazilian Amazon - Leonn Mendes Soares Pereira; Ednelza da Silva Graça Amoras; Simone Regina Souza da Silva Conde; Sâmia Demachki; Eduardo José Melo dos Santos; Sandra Souza Lima; Ricardo Ishak; Antonio Carlos Rosário Vallinoto (BMC, 2020)
Abstract Backgrounds Neural growth factor (NGF) is a neurotrophin that can interact with the p75NTR receptor and initiate a cascade of reactions that determines cell survival or death, and both are associated with the physiology of liver tissue. Single nucleotide polymorphisms (SNPs) in the NGF and p75NTR genes have been investigated in different pathologies; however, there are no studies that have analyzed their biological roles in the hepatic microenvironment. In the present study, we evaluated the impact of SNPs in these genes on the maintenance of liver function at different stages of inflammation and fibrosis in patients with chronic viral liver disease in the Brazilian Amazon. Methods The SNPs -198C > T, Arg80Gln, Val72Met, Ala35Val, Ala18Ala and Ser205Leu were genotyped by real-time PCR in samples from patients with chronic viral hepatitis stratified by stage of inflammation and liver fibrosis. Histopathological, viral load (VL), liver enzyme and comorbidities data were obtained from updated medical records. Other aspects were highlighted by applied epidemiological questionnaires. Results The -198C/T and Ala35Val polymorphisms in NGF were associated with changes in histopathological profiles, VL and liver enzymes. Ser205Leu polymorphism in p75NTR was associated only with changes in VL and liver enzymes. Polymorphic frequencies were variable among different ethnic populations, mainly for biologically relevant polymorphisms. A multifactorial network of interactions has been established based on genetic, virological, behavioral and biochemical aspects. Conclusion Mutations in the NGF (−198C > T, Ala35Val) and p75NTR (Ser205Leu) genes, within the list of multifactorial aspects, are associated with liver function in different histopathological profiles of patients with chronic viral liver disease in the Brazilian Amazon.